Transport coefficients in Yang-Mills theory and QCD - Christiansen, Nicolai; Haas, Michael; Pawlowski, Jan M.; Strodthoff, Nils (Arxiv, 2015)
We calculate the shear viscosity over entropy density ratio $η/s$ in Yang--Mills theory from the Kubo formula using an exact diagrammatic representation in terms of full propagators and vertices using gluon spectral functions as external input. We provide an analytic fit formula for the temperature dependence of $η/s$ over the whole temperature range from a glueball resonance gas at low temperatures, to a high-temperature regime consistent with perturbative results. Subsequently we provide a first estimate for $η/s$ in QCD.
Gesehen am 30.11.2017